Back Cover: Computational Insight to Improve the Thermal Isomerisation Performance of Overcrowded Alkene‐Based Molecular Motors through Structural Redesign (ChemPhysChem 21/2016). Issue 21 (7th November 2016) - Oruganti, Baswanth; Wang, Jun; Durbeej, Bo
Abstract : The Back Cover picture illustrates a new conformational strategy identified by quantum chemical calculations for accelerating and simplifying the rate‐limiting thermal isomerization steps of overcrowded alkene‐based rotary molecular motors. More information can be found in the Full Paper by B. Durbeej and co‐workers onpage 3399 in Issue 21, 2016 (DOI:10.1002/cphc.201600766 ).